Women Entrepreneurship Orientation and Marketing Capability in Driving SME Performance: Empirical Evidence from Indonesia - Nabila Kharimah Vedy (International Journal of Business Studies, 2026)
Women entrepreneurs are crucial to economic growth and household poverty reduction. However, the effectiveness of entrepreneurial orientation (EO) in improving SME performance remains inconclusive. This study examines the direct effect of EO on SME performance and the mediating role of marketing capabilities among women entrepreneurs in Indonesia. Using survey data from 131 women-owned food and beverage SMEs and Partial Least Squares Structural Equation Modeling (PLS-SEM), this study analyzes both direct and indirect effects. The results indicate that EO does not have a significant direct effect on business performance. In contrast, marketing capabilities have a positive and significant effect on performance and fully mediate the relationship between EO and performance. Among the EO dimensions, innovation demonstrates the strongest influence. These findings suggest that SME performance is driven not only by entrepreneurial orientation but also by the ability to translate it into effective marketing capabilities, highlighting the critical role of capability-based strategies in women entrepreneurship.